A novel and practical asymmetric synthesis of eptazocine hydrobromide - Li, Ruipeng; Liu, Zhenren; Chen, Liang; Pan, Jing; Lin, Kuaile; Zhou, Weicheng (Beilstein Journal of Organic Chemistry, 2018)
In order to prepare eptazocine hydrobromide effectively, a novel, mild and practical asymmetric process was developed starting from 1-methyl-7-methoxy-2-tetralone under the catalysis of N-(p-trifluoromethylbenzyl)cinchonidinium bromide. The reaction conditions were optimized to obtain the product in excellent overall yield and purity.
Keywords: alkylation; asymmetric catalysis; eptazocine; Mannich cyclization

(untitled) - Shiotani, S.; Kometani, T.; Mitsuhashi, K.; Nozawa, T.; Kurobe, A.; Futsukaichi, O. (J. Med. Chem., 1976)

(untitled) - Aceto, M. D.; Harris, L. S.; Woods, J. H.; Katz, J. L.; Smith, C. B.; Medzihradsky, F.; Jacobson, A. E.; Shiotani, S. (Jpn. J. Pharmacol., 1985)

Japanese patent - Nakamoto, Y.; Ishizuka, Y.; Takeda, S.; Yoshimura, Y. ((±)- or (+)-1-(2-N-substituted aminoethyl)-1-methyl-7-methoxy-1,2,3,4-tetrahydronaphthalenes as intermediates for eptazocine, 1989)

Eur. Patent - Hiromasa, N.; Naoyasu, I.; Shigeki, T.; Yoshifumi, Y. ((+)-or (+)-1-(2-N-substituted aminoethyl)-1-methyl-7-methoxy-1,2,3,4-tetrahydronaphthalene, and process for production thereof, 1990)

Chinese patent - Tan, H.; Zhang, G.; Cai, M.; Yuan, Q. (Method for preparation of eptazocine hydrobromide, 2015)

WO patent - Ito, T.; Liao, X. M.; Li, Z. H. (Method for producing novel 4-benzoazonine derivatives, 2017)

(untitled) - Takemoto, T.; Sodeoka, M.; Sasai, H.; Shibasaki, M. (J. Am. Chem. Soc., 1993)

(untitled) - Hulme, A. N.; Henry, S. S.; Meyers, A. I. (J. Org. Chem., 1995)

(untitled) - Shiotani, S.; Okada, H.; Yamamoto, T.; Nakamata, K.; Adachi, J.; Nakamoto, H. (Heterocycles, 1996)

(untitled) - Chen, Q.; Huo, X.; Yang, Z.; She, X. (Chem. – Asian J., 2012)

(untitled) - Shirakawa, S.; Maruoka, K. (Angew. Chem., Int. Ed., 2013)

(untitled) - Schörgenhumer, J.; Tiffner, M.; Waser, M. (Beilstein J. Org. Chem., 2017)

(untitled) - Moccia, M.; Cortigiani, M.; Monasterolo, C.; Torri, F.; Del Fiandra, C.; Fuller, G.; Kelly, B.; Adamo, M. F. A. (Org. Process Res. Dev., 2015)

(untitled) - Li, R.; Liu, Z.; Cheng, L.; Pan, J.; Zhou, W. (Beilstein J. Org. Chem., 2018)

(untitled) - Lee, T. B. K.; Wong, G. S. K. (J. Org. Chem., 1991)

(untitled) - Moss, T. A.; Fenwick, D. R.; Dixon, D. J. (J. Am. Chem. Soc., 2008)

(untitled) - Clive, D. L. J.; Sunasee, R.; Chen, Z. (Org. Biomol. Chem., 2008)

(untitled) - Clive, D. L. J.; Sunasee, R. (Org. Lett., 2007)

(untitled) - Jensen, B. L.; Slobodzian, S. V. (Tetrahedron Lett., 2000)